FLOODS AND SOCIAL VULNERABILITY: STUDY ON THE XINGU RIVER IN ALTAMIRA / PA - FRANCO,VÂNIA DOS SANTOS (2018)
Abstract The objective of this research was to classify the social vulnerability in Altamira-PA, considering the occurrence of seasonal floods and the future scenario of stabilization of the water level in the flood quota. The Social Vulnerability Index was determined by using fluviometric station data provided by ANA and socioeconomic variables from IBGE. The results indicate a moderate to low vulnerability that does not reflect the socio-spatial environment of the area, where the alert level of 6 m is recurrently exceeded during the floods of the Xingu river. The Belo Monte hydroelectric power plant will ensure the maintenance of the level of floods, which implies in the demand of urban planning that can reduce the liabilities generated by both the maintenance of wetlands, and for the extensive relocation of people, in addition by studies that assess the influence and consequence of extreme events in the region.